Preparation and characterization of macroporous bioactive glass ceramic made via sol-gel route and powder sintering method - Syed Nuzul Fadzli Syed Adam; Roslinda Shamsudin; Siti Rohani Zainuddin; Banjuraizah Johar; Firuz Zainuddin (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study was to prepare macroporous glass ceramic scaffold by sol-gel glass synthesis and powder sintering method. Sodium nitrate was added during sol-gel process to obtain glass ceramic with mol composition of 42.11% SiO2 - 18.42% CaO - 29.82% Na2O - 9.65% P2O5. The glass particles were found to be thermally stable above 900°C as indicated by TGA/DTA analysis. The dried glass particles obtained from sol-gel process were compacted and sintered at 1000°C for 3 h soaking time. Sintering crystallized the glass by 71.5% of crystallinity with tetracalcium catena-hexaphosphate (V) (Ca4(P6O19) as the main crystalline phase as revealed by XRD analysis. Although glass crystallized during sintering, it showed a good in vitro bioactivity as apatite-like layer were deposited on the glass ceramic surface when immersed in simulated body fluid (SBF) for 14 days. SEM analysis proved the macroporous structure formation with pore size ranges between 30 and 350 μm due to foaming effect which occurred during sintering. Besides that, the glass ceramic surface formed into vitrified-like due to fluxing effect during sintering thus affected the porosity and densification measurement done by Archimedes test. In conclusion, the presence of sodium oxide in sol-gel glass ceramic composition by 29.82 mol % with sintering temperature at 1000°C is able to produce bioactive and macroporous glass ceramic that potentially be used as medical scaffold material.